Indonesian Modified Clay for Dye Waste Treatment - Iwan Sumarlan; Is Fatimah; Karna Wijaya (Acta Chimica Asiana, 2020)
Synthesis and Characterization of TiO2 Coated on Clay Pillared Alumina (PILC) for Methyl Orange Photodegradation Under UV Illumination. The synthesis included both pillarization the clay with alumina and TiO2 coated on PILC using impregnation method. Some characterizations also were employed to this research such as X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), N2 Adsorption Isotherm and UV-Visible Diffuse Reflectance (DR UV). The photocatalyst was then used to decompose waste dye, methyl orange (MO). Among three photocatalysts that were successfully synthesized, PILC Ti 1.0% had the highest activity to decompose the waste dye.